Folic acid engineered sulforaphane loaded microbeads for targeting breast cancer. Issue 5 (24th March 2023) - Khan, Zafar; Alhalmi, Abdulsalam; Tyagi, Neha; Khan, Wasi Uzzaman; Sheikh, Afsana; Abourehab, Mohammed A. S.; Kohli, Kanchan; Kesharwani, Prashant
Abstract: Non-targeted cancer therapy poses a huge risk to the cancer patients' life due to high toxicity offered by chemotherapy. Breast carcinoma is one of such deleterious disease, demanding a highly effectual treatment option which could reduce the toxicity and extend survival rate. Since, folate receptors extensively display themselves on the cancer cell surface, targeting them would help to ameliorate the progression and metastasis. Considering this, we envisaged and developed sulforaphane loaded folate engineered microbeads to target breast cancer cells over-expressing folate receptors. The surface engineered microbeads were optimized and developed using emulsion gelation technique, among which the best developed preparation demonstrated the particle size of 1302 ± 3.98 µm, % EE of 84.1 ± 3.32% and in vitro drug release of 98.1 ± 4.42%@24h. The spherical sized microbead showed controlled release with improved haem-compatibility in comparison to the bare drug. Free radical scavenging activity by ABTS assay showed strong anti-oxidant activity (IC50 20.62 µg/ml) of the targeted microbeads with profound cancer cell sup pressing effect (IC50 17.48 ± 3.5 µM) as observed in MCF-7 cells by MTT assay. Finally, in comparison to lone SFN, the targeted therapy showed enhanced uptake by the intestinal villi indicating a suitable oral targeted therapy against breast carcinoma.